PENGARUH KEADILAN ORGANISASIONAL TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL KARYAWAN DI WINA HOLIDAY VILLA - Praditya, I Made Dwi Indra; Putra, Made Surya (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of organizational justice on job satisfaction and organizational commitment of employees at Wina Holiday Villa, Kuta-Bali. This research was conducted on employees Wina Holiday Villa, Kuta-Bali. Samples taken as many as 99 respondents. The samples in this study using proportional random sampling technique. Data collected by questionnaires by using a 5-point Likert scale to measure the 28 items of questions. The analysis technique used is the Path anaylsis. The analysis showed that organizational justice both positive and significant impact on job satisfaction and organizational commitment. Job satisfaction and significant positive effect on organizational commitment. The study also proved that job satisfaction mediates the effect of organizational justice on organizational commitment of employees at Wina Holiday Villa, Kuta-Bali. The hotel must always consider the level of organizational justice and job satisfaction felt by employees. It is intended that employees have a high sense of commitment to the organization
Keywords: organizational justice, job satisfaction, organizational commitment